The legal structure of the crime of abandoning the family /a comparative study - Hassan Ali Al-Tamimi , Nour; Hammad Hamid Al-Hammad, Prof. Dr.Hassan (Basra studies journal, 2022)
This study dealt with one of the important topics that is an important component of society, not the family, where the subject of the study deals (the crime of family abandonment), and this family and family abandonment may be financial and material represented in breaching the duties of spending on the family, which puts its security and stability at risk because She obtains the basic requirements of life that guarantee her continuity and permanence, food, clothing, treatment and everything necessary for living, as it may be a moral abandonment represented by a breach of the duties of education and psychological and emotional care of family members, especially children. The crime of abandoning the family is one of the social crimes stipulated by the Iraqi legislator in Chapter Eight of the Penal Code No. (111) for the year 1969 in Chapter Five under the title of crimes related to filiation, caring for a minor, endangering children and the elderly, and abandoning the family, and Article (384) stipulates: Whoever has been issued an enforceable court ruling to pay alimony to his wife, one of his ascendants, descendants, or any other person, or to perform custody, nursing, or housing, and refuses to do so while being able to do so during the month following his notification of the implementation shall be punished with imprisonment for a period of one year and a fine not exceeding one hundred dinars, or one of these two penalties. The case may only be brought on the basis of a complaint from the person concerned. It became clear to us the shortcomings of the Iraqi and Egyptian legislation in prohibiting the moral abandonment of the family, and that this shortcoming constitutes a serious deficiency in the current legislation, which the Iraqi and Egyptian legislators must avoid. But the matter is different in the Algerian legislation, as it stipulates three forms of moral abandonment of the family, and each form of them constitutes a crime: abandonment of the marital seat, abandonment of the pregnant wife, and moral abandonment of children.